Perancangan Model Basis Data Sistem Operasional Berbasiskan Customer Relationship Management - Tanty Oktavia (Bina Nusantara University, 2013)
Data is a very important asset for a company since it describes the company’s running processes. Database as a part of the information system components provides a big influence in helping data integration in a company. Therefore, we need a system which can facilitate the availability of data to be processed and used as needed, This study takes a company engaged in the sale of bike and spare parts, namely PT TDI, as the object of the study. At this time, PT TDI uses an integrated system in helping the company's operations. Along with the vision and mission, PT TDI intends to build a new operating system by applying the concept of Customer Relationship Management (CRM) which is believed to assist the company in maintaining relationships with customers using web-based platform. It aims to facilitate interaction with customers so that it can be done anytime and anywhere. This study implements the database design life cycle adjusted to the component aspects of CRM. The result achieved is a model that combines database CRM systems that can help companies improve relationships with customers.